دور تطبيق نموذج Senge في التَعَلّم التنظيمي لتحقيق الإبداع في منظمات الأعمال "مدخل إلى دراسة تفكير النظم" - دباس هاشم فوزي; سلطان يوسف حجيم (Journal of Economics and Administrative Sciences, 2008)
The purpose of this research is to suggest a model which may be used by law enforcement to broaden individual and organizational creativity while providing a more inclusive, holistic view of management within our internal and external organizational structures. This project introduces alternatives to traditional management, leadership styles and problem solving strategies. Law enforcement organizations in the 21st century will face many challenges. Much like community policing impacted the nation in the mid 1980’s through the 1990’s, the systems thinking approach offers a philosophy for the new millennium. Most organizations will face many challenges in the next decade of the twentieth first century. Just as happened in the mid-1980’s to end 1990’s of the twentieth century, when influenced policy pursued by some organizations using some modern management methods at that time, and the concept of systems thinking presents new philosophy for the new millennium. By using models such as the concept of theoretical model systems of (Senge 1994), which will address in this research, and therefore can achieve a broader viewpoint and new results in the case of application in business organizations. Of course, the session of systems thinking do not end and will continue. Once collective thinking generated we could say that all individuals are participating in the management process and in all its details. It was summed systems thinking model in this research by using the principles of Organization learning (Senge, 1994) due to its close to the facts of application of individual and organizational creativity. Through personal mastery, shared vision, team learning, and examination of mental models through thinking systems, we can learn new ways of thinking and acting, and collective action, in actual meaning and purpose.